Support System for Gifted Children and Youth in Conditions of Additional Education - Mishina M. M. (Psychological and Pedagogical Support of Talented Children: Problems, Directions, Approaches, Conditions, 2020)
the article deals with the problem of support and accompaniment of gifted children and youth by introducing a course of classes on the development of cognitive abilities that develop personality, taking into account the professional orientation of students, into the training program of the State Autonomous Educational Institution of Additional Education "Center for gifted children "Poisk" in Stavropol. The course program "Intellectual Labor Techniques" provides psychodiagnostics and further development of cognitive abilities, taking into account the interests, aptitudes and personal characteristics of gifted children and youth. The purpose of the research is to study the impact of purposeful formation of cognitive abilities on the personal development of gifted children and youth.
Keywords: педагогическая деятельность; дополнительное образование; формирование; formation; additional education; система поддержки одарённых детей и молодежи; support system for gifted children and youth; pedagogical activity